Limited hydrolysis combined with controlled Maillard-induced glycation does not reduce immunoreactivity of soy protein for all sera tested. (15th December 2016) - Walter, Jordan; Greenberg, Yana; Sriramarao, P.; Ismail, Baraem P.
Highlights: Determined the effect of proteolysis and glycation on soy protein immunoreactivity. Response surface methodology provided optimized hydrolysis conditions. Glycation may reduce or increase immunoreactivity of SPH based on the serum used. Results revealed mixed observations attributed to differences in the sera used. Abstract: Combining proteolysis and Maillard-induced glycation was investigated to reduce the immunoreactivity of soy protein. Soy protein was hydrolyzed by Alcalase following response surface methodology utilizing three variables, temperature, time, and enzyme:substrate ratio, with the degree of hydrolysis (DH) and percent reduction in immunoreactivity as response variables. Western blots and ELISA were used to evaluate immunoreactivity using human sera. Data were fitted to appropriate models and prediction equations were generated to determine optimal hydrolysis conditions. The hydrolysate produced under optimized conditions was subjected to glycation with dextran. Hydrolysate produced under optimal conditions had 7.8% DH and a percent reduction in immunoreactivity ranging from 20% to 52%, depending on the sera used. Upon glycation, immunoreactivity was further reduced only when using serum that had the highest soy-specific IgE. This work revealed limitations and provided premises for future studies intended to prove the potency of the combined modification approach to produce a hypoallergenic protein ingredient.